Editorial - Kennedy, Dr S Hanuman (Ushus Journal of Business Management, 2016)
This issue largely focuses on the topics related to general management. The first article on ‘Impact of Innovative Strategic Human Resource Management Practices on the Performance of Small and Medium Enterprises’– A Case Study of Karnataka by B.K.Sathyanarayana and Nawal Kishor aims at evaluating the application and implementation of Strategic Human Resource Management (SHRM) practices for Small and Medium Enterprises (SMEs) and to examine its impact on organisational performance. Six hundred & forty SMEs in and around the Bangalore District from both Manufacturing and Services Sector responded to the various Strategic Human Resource Management drivers and organizational drivers and it was inferred that there exists a positive significant correlation between these variables. The next article on sustainable development best management practices in the food processing industry by Uma CS, Basavaraj & Prasanna Joshi attempts to study sustainable development that involves issues like organic farming, food safety and food quality. This paper highlights on the concept of green food system and the approach of good agricultural practices (GAP) which is a new concept that stresses on international quality standards, concerns and commitments about food production, food safety and security, environment sustainability of agriculture. Quality management is equally important in the food industry. Food processing is a capital intensive, water consuming and a polluting industry. Therefore this paper also studies the management practices in this industry to reduce water wastage, ensuring food quality so the concept of green growth can be achieved. It also throws light on the various Governmental laws and regulations passed to control pollution and ensure food quality and health of the people.